Perkembangan Tingkat Kemiskinan Dan Kesenjangan Sosial Regional Di Indonesia 2011-2015 - Iwan Prasodjo (Jurnal Ekonomi, 2017)
This article discusses on poverty rate and inequality in urban and rural areas during 2011-15. It shows that poverty rate tends todecrease. The poverty in rural area is worse than that in the urban one. The urban poor people work in the informal sector or in the small business. The poor in the rural areas work in the agriculture sector. The majority of poorest provinces is in the east Indonesia. However, the majority of the poor people live in Java island. Eventough the income inequility in Indonesia is moderate, but it Â has been increased since 2011. There are many more poor people above the national poverty line. The government could inprove rural and east Indonesia infstructure in order to increase agriculture production. In this way the poverty in rural area and the gap between east and west Indonesia could decrease.